The legality of a Jewish state : a century of debate over rights in Palestine / John Quigley, Ohio State University. - Quigley, John B. (Cambridge University Press, 2022)
In The Legality of a Jewish State, the author traces the diplomatic history that led to the partition of Palestine in 1948 and the creation of Israel as a state. He argues that the fate of Palestine was not determined on the basis of principle, but by the failure of legality. In focusing on the lawyer-diplomats who pressed for and against a Jewish state at the United Nations, he offers an explanation of the effort in 1947-48 by Arab states at the UN to gain a legal opinion from the International Court of Justice about partition and the declaration of a Jewish state. Their arguments at that time may surprise a twenty-first-century reader, touching on issues that are still at the heart of the contemporary conflict in the Middle East.